The placebo effect in sports performance: A brief review - Beedie, C. J.; Foad, A. J. (Sports Medicine, 2009)
The placebo effect, with its central role in clinical trials, is acknowledged as a factor in sports medicine, although until recently little has been known about the likely magnitude and extent of the effect in any specific research setting. Even less is known about the prevalence of the effect in competitive sport. The present paper reviews 12 intervention studies in sports performance. All examine placebo effects associated with the administration of an inert substance believed by subjects to be an ergogenic aid. Placebo effects of varying magnitudes are reported in studies addressing sports from weightlifting to endurance cycling. Findings suggest that psychological variables such as motivation, expectancy and conditioning, and the interaction of these variables with physiological variables, might be significant factors in driving both positive and negative outcomes. Programmatic research involving the triangulation of data, and investigation of contextual and personality factors in the mediation of placebo responses may help to advance knowledge in this area.